Language Learning Media Through Mobile APP: The Effects of Busuu on Vocabulary Learning and Listening Skills - Nadya, Laela Nada; Aswir, Aswir (Published by Institut Teknologi Pendidikan Indonesia, 2023)
This study investigates the effects of the Busuu Mobile app on vocabulary learning and listening skills. In order to achieve the objective of this study, the researchers used a quantitative approach with a pre-experimental design. The participants of this study were 38 students of class 7.1 in SMP Negeri 4 Tangerang Selatan, with a total of 469 populations. The data were collected through pre-tests and post-tests to determine students’ vocabulary learning and listening skills scores. The scores were then analyzed using Paired Sample Effect Size to determine the effects’ significance. The effect size of students’ vocabulary learning and listening skills was high, with 4.404 for vocabulary learning and 4.670 for listening skills (>1). This study concludes that using Busuu on students’ vocabulary learning and listening skills had a high effect. Therefore, the Busuu mobile app is advised to be utilized in vocabulary learning and listening skills. The future study of finding out the students’ perception of using Busuu will be necessary for the effectiveness of using this mobile application.